Building a Church of Liberation: Orthopraxis as the Public Shape of the Church's Common Good - Dávila, MT (Journal of the Society of Christian Ethics, 2022)
Examining the ethics of the church as an institution necessarily asks what can serve as criteria or ultimate aims for the functioning of institutions responsible for nourishing and supporting Christian witness in society. For liberation theology and ethics, orthopraxis—righteousness in the practices both within and outside the church for the sake of becoming the church of the poor—becomes such criteria. Becoming a church of liberation, the church of the poor, allows us to evaluate the church as an institution or polis with a particular common good that ought to be shaped for and put at the service of prophetic Christian witness. Recent crises and challenges in the life of the Christian churches in the United States help ground this proposal in the author's specific context.